2020
DOI: 10.1101/2020.01.18.911396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multidimensional hydrogel models reveal endothelial network angiocrine signals increase glioblastoma cell number, invasion, and temozolomide resistance

Abstract: Glioblastoma is the most common primary malignant brain tumor. The tissue microenvironment adjacent to vasculature, termed the perivascular niche, has been implicated in promoting biological processes involved in glioblastoma progression such as invasion, proliferation, and therapeutic resistance. However, the exact nature of the cues that support tumor cell aggression in this niche are largely unknown. Soluble angiocrine factors secreted by tumor-associated vasculature have been shown to support such behavior… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Here, we report a multidimensional hydrogel platform to examine pathophysiological processes linked to GBM progression and mortality using patient-derived GBM specimens in response to microglia. We have also recently described hydrogel-based platforms to investigate the role of angiocrine signaling from engineered perivascular cultures on GBM cell invasion and resistance to the frontline chemotherapy temozolomide [57]. We also reported adaptations to the hydrogel environment via localized formation of hypoxic zone to support culture of a broader diversity of cells from the neurovascular unit [58].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Here, we report a multidimensional hydrogel platform to examine pathophysiological processes linked to GBM progression and mortality using patient-derived GBM specimens in response to microglia. We have also recently described hydrogel-based platforms to investigate the role of angiocrine signaling from engineered perivascular cultures on GBM cell invasion and resistance to the frontline chemotherapy temozolomide [57]. We also reported adaptations to the hydrogel environment via localized formation of hypoxic zone to support culture of a broader diversity of cells from the neurovascular unit [58].…”
Section: Discussionmentioning
confidence: 97%
“…We have previously developed a family of gelatin hydrogels to investigate pathophysiological processes underlying glioblastoma invasion and progression. Extensive biophysical performance data has previously been reported including network architecture and mechanical performance [52,53], water and small-molecule diffusivity [54][55][56], and the capacity to support growth and phenotypic studies of primary glioblastoma cells and cells from the neurovascular unit [57,58]. For this project, GBM and MG cells were maintained in three-dimensional culture in a 4 wt% methacrylamide-functionalized gelatin (GelMA) that exhibited a physiologically relevant Young's modulus (1.04 ± 0.10 kPa; n = 14; Fig.…”
Section: Co-culture System Assembly and Mechanical Testing Of Gelma Hmentioning
confidence: 99%
See 1 more Smart Citation
“…43 More recently, we showed 20 paracrine signals from marrow-derived mesenchymal stem cells could enhance the retention of quiescent HSCs, 26 though this effect was also strongly dependent on the relative ratio of HSCs to MSCs as well as on processes of MSC-mediated hydrogel remodeling. Separately, a wide range of studies have focused on developing microphysiological models of the perivascular environment to interrogate processes associated with disease progression, 9,29,54,55 cancer invasion or metastasis, 4,37,50,51,66 and even dormancy of cancer stem cells. 10,24 These studies provide an illustrative example of the power of the perivascular environment and motivate our study of the role of perivascular signals on murine HSC culture.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we observed that biophysical (hyaluronan content and molecular weight) and metabolic (hypoxia) transitions in the GBM tumor microenvironment both significantly alter GBM invasion [30][31][32]. More recently, we adapted this system to profile cytokine-based crosstalk between cells within the GBM tumor microenvironment, identifying secreted factors generated by an artificial perivascular niche that can accelerate GBM cell invasion [33]. The objective of the present study was to adapt this established hydrogel platform and cytokine analysis protocols to examine the effects of microglia within the GBM tumor microenvironment on GBM gene expression and invasiveness using patient-derived GBM specimens that maintain patient-specific morphologic and molecular phenotypes [34,35].…”
Section: Introductionmentioning
confidence: 99%